2015
DOI: 10.1093/molbev/msv012
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Active Maintenance of Phylotranscriptomic Hourglass Patterns in Animal and Plant Embryogenesis

Abstract: The developmental hourglass model has been used to describe the morphological transitions of related species throughout embryogenesis. Recently, quantifiable approaches combining transcriptomic and evolutionary information provided novel evidence for the presence of a phylotranscriptomic hourglass pattern across kingdoms. As its biological function is unknown it remains speculative whether this pattern is functional or merely represents a nonfunctional evolutionary relic. The latter would seriously hamper futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
143
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(163 citation statements)
references
References 51 publications
10
143
1
Order By: Relevance
“…Furthermore, adding extraneous genomes effectively dilutes the database, such that more similarity is needed to pass an E-value threshold. Because we included only a sample of non-hymenopteran genomes, we were therefore able to stringently identify orthologs (E-value 10 -10 in comparison to a typical value of 10 -5 ) 81 and accurately place them along the hymenopteran phylogeny.…”
Section: Phylostratigraphymentioning
confidence: 99%
“…Furthermore, adding extraneous genomes effectively dilutes the database, such that more similarity is needed to pass an E-value threshold. Because we included only a sample of non-hymenopteran genomes, we were therefore able to stringently identify orthologs (E-value 10 -10 in comparison to a typical value of 10 -5 ) 81 and accurately place them along the hymenopteran phylogeny.…”
Section: Phylostratigraphymentioning
confidence: 99%
“…Despite the repeated observation that late development is highly divergent for diverse genomic properties (sequence evolution, duplication, gene age, expression divergence) in diverse animal species (Roux and Robinson-Rechavi 2008;Domazet-Loso and Tautz 2010;Kalinka et al 2010;Irie and Kuratani 2011;Levin et al 2012;Piasecka et al 2013;Drost et al 2015;Liu and Robinson-Rechavi 2017), the underlying evolutionary forces driving such a pattern remain obscure. The "developmental constraint" hypothesis suggests that this high divergence is due to relaxed purifying selection, whereas Darwin's "selection opportunity" hypothesis proposes stronger positive selection (as discussed in Artieri et al 2009;Kalinka and Tomancak 2012 Artieri et al 2009;Kalinka et al 2010).…”
Section: Developmental Constraint Hypothesis and Darwin's Selection Omentioning
confidence: 99%
“…Based on recent genomic studies, both models have some level of molecular support. Some studies support the early conservation model (Roux and Robinson-Rechavi 2008;Artieri et al 2009), while most recent ones support the hourglass model (Kalinka et al 2010;Irie and Kuratani 2011;Levin et al 2012;Quint et al 2012;Drost et al 2015;Hu et al 2017;Zalts and Yanai 2017). And in fact the two models may not be mutually exclusive (Piasecka et al 2013;Liu and Robinson-Rechavi 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in vertebrates (zebrafish) and insects (Drosophila melanogaster) confirmed this hypothesis because genes expressed during the phylotypic stage were more conserved and less rapidly evolving than genes expressed in other stages of development (Domazet-Lo so and Tautz 2010; Kalinka et al 2010). Although plants do not have a clear morphologically defined phylotypic stage, a transcriptomic hourglass was also postulated for the model plant Arabidopsis thaliana because old and slowly evolving genes contribute disproportionally to the overall transcriptome during early stages of embryo development (Quint et al 2012;Drost et al 2015), but see Piasecka et al (2013).…”
Section: Introductionmentioning
confidence: 97%